Pengaruh Motivasi Kerja, Kompetensi dan Lingkungan Kerja Non Fisik terhadap Kepuasan Kerja Karyawan pada PT. Sang Tunas Sejahtera di Denpasar - Setyari, Ari Setyari Ari; Sugianingrat, I.A Putu Widani (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Jobs satisfacations cans bes defineds ass thes level of effectiveness or emotionals response to various aspects of one's works. A set of feelings that employees have about whether their work is enjoyable or not. Many factors, including motivation to work, competences, and nosn-physicasl work environmenst, influences josb satisfaction. Thes focus of this researchs is to fiind out hows work motivatiion, competences, and the non-physicals work environments influence job satissfaction. This researchs wass conductesd at PT. Sang Tunas Sejahtera in Denpasar, and the sample used was 45 respondents. Classsical Assumptionss, Multiples Linearss Regression, Coefficients of Determinations, and t-test and F-tesst weres useds to analyzes the data. The ressearchs resultss show thats work motivation has a positives effects on job satissfaction, competence hass a possitive effects on jobs satissfaction, ands the nosn-physicasl work environmenst has a possitive effects on job satissfaction. Apart from that, work motivation, competence, and the non-physsical work environments have a positives effect on job ssatisfaction ssimultaneously. The independents variabel thats has the greatesst influences on job satisfactions is 60.3%.